Implications of adopting drip irrigation system on crop yield and gender-sensitive issues: The case of Haramaya District, Ethiopia - Meseret Dawit; Megersa Olumana Dinka; Olkeba Tolessa Leta (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Integration of advanced irrigation systems and technology is essential to improve crop water productivity and yields, especially in developing countries. This study aims at investigating the effects of adopting a drip irrigation system combined with hand-dug wells on crop water productivity and yields of household farmers and their perception on the proposed scheme over two cropping seasons in the Haramaya District, Ethiopia. We chose three locally called "Kebeles" within the District, and selected a certain number of household farmers that had similar characteristics within each Kebele. The selected farmers had practiced both the proposed drip irrigation with private hand-dug wells water supply (intervention pilots) and traditionally-used surface irrigation with communal water supply (non-intervention pilots) schemes. We also conducted interviews with the selected household farmers, personal observations, and measurements on crop water productivity and yields for both intervention and non-intervention pilots. We found that the proposed drip irrigation system significantly improved the crop productivity and yields of the farmers. More importantly, findings indicated that the use of drip irrigation system combined with hand-dug well water supplies reduced the over-exploitation of water (water savings) and labor-intensive manual-irrigation. The latter particularly helped women to work less on their farm works and thus provided them a flexible system to expand their plot sizes and grow a variety of crops. Overall, the drip irrigation system with water supply from hand-dug wells is highly recommended as it allows a flexible system for household farmers and provides an opportunity to expand their plot sizes with a variety of crops, which is also expected to mitigate the negative implications of climate change on freshwater water resources and crop productivity. However, the farmers of the Haramaya District expressed their need on capacity building, financial and technical supports from local to regional governments and other agencies to ensure an efficient and cost-effective drip irrigation system and to further improve their crop water productivity and yield, food self-sufficieny, and livelihoods. It is also important to consider market-based farming approaches, while promoting efficient irrigation systems and self-supply to ensure quick investment returns. This study recommends to adopt and expand the proposed drip irrigation system at household levels in Sub-Saharan and other similar regions.
Keywords: 650; drip irrigation; crop yield; Haramaya District; household farmers; hand-dug wells